2016
DOI: 10.1111/nep.12890
|View full text |Cite
|
Sign up to set email alerts
|

Initiation time of renal replacement therapy on patients with acute kidney injury: A systematic review and meta‐analysis of 8179 participants

Abstract: ABSTRACT:The early initiation of renal replacement therapy has been recommended for patients with acute renal failure by some studies, but its effects on mortality and renal recovery are unknown. We conducted an updated meta-analysis to provide quantitative evaluations of the association between the early initiation of renal replacement therapy and mortality for patients with acute kidney injury. After applying inclusion/exclusion criteria, 51 studies, including 10 randomized controlled trials, with a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…The results of both studies are obviously not comparable due to high discrepancies in study design, and they both do not arrive at definitive conclusions. However, these findings together with the results of a recently performed meta-analysis (15) suggest that "early" initiation of renal replacement therapy might improve the survival of critically ill patients with acute kidney injury. Future multicenter randomized controlled studies are requested not to focus only on mortality but also on renal recovery and progression of acute kidney injury to chronic kidney disease.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…The results of both studies are obviously not comparable due to high discrepancies in study design, and they both do not arrive at definitive conclusions. However, these findings together with the results of a recently performed meta-analysis (15) suggest that "early" initiation of renal replacement therapy might improve the survival of critically ill patients with acute kidney injury. Future multicenter randomized controlled studies are requested not to focus only on mortality but also on renal recovery and progression of acute kidney injury to chronic kidney disease.…”
mentioning
confidence: 90%
“…The only available treatment option of severe acute kidney injury in critically ill patients is renal replacement therapy (1,2). However, a number of issues affecting the optimal use of this primarily supportive technique still remain unresolved (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite previous studies investigating the relationship between mortality and the timing of RRT initiation, it remained controversial whether early initiation of RRT improved outcomes. In 2016, two RCTs and in 2017 nine systematic reviews and meta‐analyses evaluated the optimal timing of RRT initiation for AKI. A multicenter RCT study, the Artificial Kidney Initiation in Kidney Injury (AKIKI) study, conducted in France, showed that there were no significant differences in mortality between early and late initiation of RRT .…”
Section: Rrt For Akimentioning
confidence: 99%